The Challenge to Restoring Basic Health Care in Uganda - Okello, D. O.; Lubanga, R.; Guwatudde, D.; Sebina-Zziwa, A. (Social Science & Medicine, 1998)
This paper presents the results of a health facility survey conducted in Uganda between June 1992 and December 1993. The survey covered both government and non-government organisation (NGO) facilities from 10 districts in the five regions of the country. The main objective of the survey was to assess resource use, costs and financing of health facilities. The survey found differences between resource levels of NGOs and government facilities. Government facilities were inadequately maintained, and mostly in a state of disrepair. The user fee scheme that had been recently introduced in some government units to meet running costs was not only inadequate, but was not being used to meet the needs of consumers. In addition, most available resources, including human resources, were concentrated in hospitals. As a result, there was heavy demand for hospital services and less use of services in the lower level facilities. And furthermore, staff in government facilities were paid much less than staff working for NGOs, who not only got better pay but also in-kind forms of rewards, which made them better motivated to work. The number of qualified staff, particularly for primary health care, was grossly inadequate, and most of the work in local facilities was being done by unqualified employees, such as ward maids and dressers. In order to alleviate some of the problems identified, particularly in government facilities, there is a need to explore ways in which more can be done with the available resources to improve the efficiency of health services. The user charge system could be effective in improving the resource base of the health facilities, but it must result in visible improvement in the quality of services for consumers to be willing to pay. Collection methods should be standardized, and expenditures supervised. As part of the government's decentralization programme, districts should be given the power to recruit and fire personnel. Once this authority is in place, the district should consider employing fewer personnel at all levels and aim to pay them a living wage.
Keywords: Challenge; Restoring Basic Health Care; Uganda